Nutrient availability challenges the sustainability of low-input oil palm farming systems - Damien Marie Essono; Baruch Batamack Nkoué; Eric Voundi; Léon Kono; Eric Verrecchia; Jaboury Ghazoul; Armand William Mala; Alexandre Buttler; Thomas Guillaume (Farming System)
The social and economic benefits for smallholders cultivating oil palms are usually associated with environmental degradation and high resource consumption inherent to intensive farming systems. Nonetheless, the extensification of agricultural practices by many smallholders due to limited access to funds, agricultural inputs, or knowledge may result in a more environmental-friendly oil palm production. Here, we assessed the trade-offs between production and soil degradation in two oil palm farming systems established on forested land in the Ngwei region (Cameroon) comparing practices with no (smallholder system, SH) and low (elite system, EL) agricultural inputs (fertilizer, herbicides). Soil characteristics, nutrient deficiencies and oil palm production were determined in forty-two plantations of different age covering one full plantation cycle. The rates of soil organic carbon (SOC) loss were similar in both farming systems (−0.029 ​± ​0.012 ​kg ​C m−2 yr−1), but soil bulk density and pH were not affected by the forest conversion. Soil available potassium (K) decreased sharply during the first 7.3 ​± ​0.9 years before stabilizing. Potassium fertilization limited leaflet K deficiencies during the immature phase in EL, but was not sufficient to prevent K deficiencies during the production phase, reaching similarly low K nutrition index as in SH (0.68 ​± ​0.13). Oil palm growth was similar in both systems, but fresh fruit bunches (FFB) production was enhanced by 38 ​± ​11% in EL. The nitrogen (N) deficiencies were pronounced in both systems. However, the higher biomass export in EL induced phosphorus depletion in soils and reinforced N depletion as compared to SH. Despite limited soil degradation, nutrient depletion in the agroecosystem threatens the sustainability of these two low-input oil palm farming systems. This calls for optimization, such as a targeted intensification in the EL system and a reduced oil palm density in the SH system.